LEGAL CERTAINTY AND THE LIMITATION OF FULL ASSET HIBAH TO NON-MARITAL CHILDREN: A COMPARATIVE ANALYSIS OF THE INDONESIAN CIVIL CODE, COMPILATION OF ISLAMIC LAW, AND AHKAM HADITH - Zuhairiah Zuhairiah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the legal certainty surrounding the transfer of 100% of assets through hibah Indonesian Civil Code (ICC), the Compilation of Islamic Law (CIL), and the perspective of Ahkam Hadith. This issue arises from the inherent tension between the principle of freedom of property disposition and the protection of heirs’ compulsory shares (legitime portie). This research adopts a normative juridical approach with a comparative method, focusing on the synchronization between positive legal norms and their underlying theological foundations. The findings reveal that Article 913 of the ICC permits the filing of a reduction claim (inkorting) when a grant infringes upon the compulsory portion of heirs. From an Islamic legal perspective, the CIL imposes limitations on hibah to prevent prejudice against heirs, in line with the principles derived from Ahkam Hadith, particularly the hadith of Nu’man bin Bashir, which emphasizes justice (al-‘adl) among children and the prohibition of harm. Furthermore, the limitation of one-third of the estate in Islamic legal practice reinforces the restriction against total transfers that may eliminate legitimate inheritance rights. This study concludes that the transfer of 100% of assets to a child born out of wedlock potentially creates legal uncertainty and increases the risk of annulment of the notarial deed. Therefore, notaries play a crucial role in mitigating such risks through the incorporation of preventive clauses in legal instruments, ensuring legal protection and alignment with principles of justice in Islamic law, thereby minimizing the likelihood of future disputes